Penerapan Sistem Pelaporan Mandiri Kebersihan Lingkungan dan Pemantauan Jentik Nyamuk - Sri Lestari; Wieko Wieko; Muhammad Adri Ramadhan; Muhammad Zaeni Nadip (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This research aims to address issues in environmental cleanliness management and mosquito larvae monitoring in Malaka Jaya, East Jakarta. The expected solution is the development of a web-based application that facilitates real-time reporting and monitoring. The research object includes local communities and sanitation officers. The methods employed involve prototype application development,  black-box testing, and user socialization. The research results indicate that the application functions effectively, enhancing reporting efficiency and community awareness of environmental cleanliness. The conclusion drawn from this study is that the application can serve as an effective tool in cleanliness management and disease prevention. The implications of this research highlight the need for continuous development and integration with other technologies to improve system effectiveness. Recommendations include community education and impact evaluation of the application post-implementation.   Keywords: Application, Community Participation, Environmental Cleanliness, Mosquito Monitoring